KEPEMIMPINAN KEPALA SEKOLAH DALAM MEWUJUDKAN SEKOLAH SEBAGAI KOMUNITAS BELAJAR YANG BERKELANJUTAN - Nawireja, Iman Kasiman; Simanjuntak, Clara Yolanda; Hutahaean, Markus Amartya Sam; Leriya, Della; Putri, Nadhira Aisha; Ananda, Tri; Putra, Rizki Aditya (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Transformation learning has a crucial role for both educators, support staff, learners and other related parties in creating a participatory and inclusive education environment. Educational environment that is participatory and inclusive. This research examines the role of leadership role of the principal in realizing the school as a sustainable learning community in SMA Negeri 1 Ciampea, Bogor Regency. learning community at SMA Negeri 1 Ciampea, Bogor Regency. This research uses a qualitative approach, where data is collected through observation, in-depth interviews, as well as literature studies on journals and related research. The research period lasted from August to October 2024. Research findings show that school principals have a central role in adapting educational changes, such as the implementation of the Merdeka Curriculum and the development of extracurricular programs. changes in education, such as the implementation of Merdeka Curriculum and the development of extracurricular programs to support students' talents and interests. to support students' talents and interests. In addition, literacy programs, religious religious activities and character education contribute to creating an inclusive and participatory school culture. School culture that is inclusive and participatory. This research also reveals the challenges in transformation of learning, including the use of technology in the utilization of technology in the teaching process and improving the quality of educators.